(untitled) (Global Conference on Medical and Health Sciences, 2026)
Critical neurological conditions, including traumatic brain injury, stroke, status epilepticus, and coma, are associated with high morbidity and mortality rates worldwide. Early detection of secondary brain injury and timely intervention remain crucial challenges in neurocritical care. In recent years, advanced neurophysiological monitoring techniques—such as electroencephalography (EEG), intracranial pressure (ICP) monitoring, brain tissue oxygenation (PbtO₂), and multimodal neuromonitoring—have emerged as essential tools for real-time assessment of brain function. This study aims to explore the predictive value of advanced neurophysiological monitoring in critically ill neurological patients and evaluate its role in improving clinical outcomes.